Cosmic Hunt, Copper Electroplating, Chaosmic Transduction: Chaosmotechnics of Molecular Collaboration in Matthew Barney’s Redoubt Project (2016–21) - Przedpełski, Radek (Text Matters: A Journal of Literature, Theory and Culture, 2023)
The article considers Matthew Barney’s artistic project Redoubt (2016–21) from the point of view of Gilbert Simondon’s transductive philosophy of individuation. Informed by Simondon—read here with Félix Guattari, Gilles Deleuze and Yuk Hui—the article performs a case study of Barney’s long-term, expansive and multi-layered project. Redoubt comprises a feature-length film, metal reliefs, and large-scale sculptures, as well as an intermedial performance. The article focuses on the mythological theme of the Cosmic Hunt deployed in Barney’s eponymous feature film as well as on his experimental artistic process entailing cast metals. The goal of the article is to provide a diagram of the functioning of Barney’s complex conception of metamorphosis, which plays itself out on many—heterogenous, yet ultimately entangled—orders of magnitude. Consideration will also be given to the political and decolonial implications of Barney’s artistic proposal, which liberate the notion of the hunt from its takeover by colonial extractivism in order to reveal it as an intensive capture of forces.